Two new species of the Clistopyga henryi species-group (Hymenoptera, Ichneumonidae, Pimplinae) from South America, with a key to species of the group - Pádua, Diego G.; Sääksjärvi, Ilari E.; Kaunisto, Kari M.; Monteiro, Ricardo F. (Pensoft Publishers, 2026)
The Neotropical Clistopyga henryi species-group includes currently four described species. In this study, we describe two new species (C. peruandina Sääksjärvi & Pádua, sp. nov. and C. teresopolitana Pádua, sp. nov.) from the Peruvian Andes and Brazilian coastal rainforests. In addition, we provide information on the variation of C. carinata Bordera & Palacio and a key to species of the species-group.